Reduced genetic variability within coding and non-coding regions of the echinococcus multilocularis genome - Haag, Karen Luisa (1997)
Echinococcus multilocularis, a vulpine intestinal tapeworm, is the causative agent of alveolar echinococosis in humans, one of the most severe and lethal parasitic infections in man. To date, there is very little knowledge about the genetical polymorphism of this parasite. To assess sequence polymorphism, we analysed a sample of 33 E. multilocularis isolates from Europe, North America and Asia by PCR-SSCP followed by nucleotide sequencing. This assessment was performed comparatively to sheep, cattle and pig E. granulosus strains. Coding (nuclear antigen B and mitochondrial NADH dehydrogenase genes) and non-coding (introns of actin and homeobox-containing genes) regions of the parasite genome were chosen as targets. Since the estimated nucleotide diversity among genotypes of E. multilocularis were, in general, 10 times lower than among the recognized different strains of E. granulosus, we suggest that the conventional classi®cation of the former species in 2 separated strains (European and North American) should be reviewed.